2011
DOI: 10.1055/s-0031-1295415
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of rh-TSH and Thyroid Hormone Withdrawal in Patients with Differentiated Thyroid Cancer: Preliminary Evidence for an Influence of Age on the Subjective Well-being in Hypothyroidism

Abstract: We aimed to investigate the subjective well-being in patients with differentiated thyroid cancer after hormone withdrawal. Since this might be confounded by psycho-oncological processes unrelated to hypothyroidism we intended to minimize such factors by only including patients with a history of uneventful follow-up examinations for several years. We investigated 67 patients applying the General Health Questionnaire (GHQ-12) at 3 time points t1, t2, and t3. The time point t2 represented an intensified follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Our findings, that younger persons are more impaired than older subjects after thyroid hormone withdrawal is in accordance with recent findings by Heinzel et al, who reported a stronger subjective impairment in younger patients after thyroid hormone withdrawal than in older patients (46). This is in accordance with observations of age-dependent effects on heart action potential parameters observed to parallel age-related thyroid states (47,48).…”
Section: Hypothyroidsupporting
confidence: 94%
“…Our findings, that younger persons are more impaired than older subjects after thyroid hormone withdrawal is in accordance with recent findings by Heinzel et al, who reported a stronger subjective impairment in younger patients after thyroid hormone withdrawal than in older patients (46). This is in accordance with observations of age-dependent effects on heart action potential parameters observed to parallel age-related thyroid states (47,48).…”
Section: Hypothyroidsupporting
confidence: 94%
“…Besides the somatic symptoms of hypothyroidism, the subjective perception of quality of life is considerably better in patients treated with rhTSH than in patients after thyroid hormone withdrawal (1,2). This is especially true in younger patients with DTC (3).…”
Section: Introductionmentioning
confidence: 99%
“…Serum thyroglobulin determination is the pivotal tool during follow-up of patients treated for differentiated thyroid cancers [1]. After thyroid cells ablation by thyroidectomy and radioiodine, as verified by whole body scan (WBS), Tg is expected to be undetectable; consequently, detectable Tg levels may indicate tumor recurrence or metastasis [26][27][28]. In addition, Tg measurement has been ascribed as a potential predictor of malignancy in patients with thyroid nodules with controversial data.…”
mentioning
confidence: 99%